Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10164-008-0100-5
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of chemical stimuli in conspecific fecal pellets by a visually adept iguanid lizard, Crotaphytus collaris

Abstract: Iguanid lizards are known for visual acuity and a diminished vomeronasal organ, which has led to mixed conclusions on whether iguanids use chemical cues. The collared lizard, Crotaphytus collaris, is a territorial iguanid that lives in open rocky habitats. Fecal pellets placed prominently on open rocky perches may provide an ideal mechanism for intraspecific chemical signaling. In order to determine whether collared lizards can discriminate between chemical stimuli found in conspecific fecal pellets, we collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
14
0
1
Order By: Relevance
“…; López & Martín ). Chemoreception may be less well developed in iguanian lizards that employ their highly developed vision to detect approaching prey while scanning from elevated perches that are then captured using short chases (Evans ; Wilgers & Horne ). In many iguanians, selection has favored social signals involving conspicuous coloration and stereotypical displays that are transmitted visually (Shine ; Baird et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; López & Martín ). Chemoreception may be less well developed in iguanian lizards that employ their highly developed vision to detect approaching prey while scanning from elevated perches that are then captured using short chases (Evans ; Wilgers & Horne ). In many iguanians, selection has favored social signals involving conspicuous coloration and stereotypical displays that are transmitted visually (Shine ; Baird et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, experimental studies have shown that chemical secretions function in species recognition, advertisement of resource holding power to same-sex rivals, courtship signals to potential female mates, recognition of familiar vs. unfamiliar rivals, and even recognition of individuals (Mart ın & L opez 2007;Carazo et al 2008;Font et al 2012;L opez & Mart ın 2012). Chemoreception may be less well developed in iguanian lizards that employ their highly developed vision to detect approaching prey while scanning from elevated perches that are then captured using short chases (Evans 2003;Wilgers & Horne 2009). In many iguanians, selection has favored social signals involving conspicuous coloration and stereotypical displays that are transmitted visually (Shine 1990;Baird et al 2012), perhaps as a consequence of selection for the acute vision required for sit-and-wait foraging tactics.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical communication in other iguanids is mediated by lizard's depositions (Labra, 2007;Wilgers and Horne, 2008). Neither depositions nor typical recognition behaviors (tongue flicking and gular pump) were identified during the trials which suggest chemical communication may not be relevant to our study.…”
Section: Discussionmentioning
confidence: 61%
“…There is good evidence that many species of lizards use chemical cues for some form of communication (Quinn and Hews, 2005;Labra, 2007;Wilgers and Horne, 2008), potentially affecting the behavior of individuals during the trials. Chemical communication in other iguanids is mediated by lizard's depositions (Labra, 2007;Wilgers and Horne, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…No trabalho de BULL e colaboradores (1999b) há indícios de que os semioquímicos presentes nas fezes compreendem compostos lipofílicos, uma vez que machos responderam às fezes quando dissolvidas em diclorometano, mas não o fizeram quando as fezes foram apresentadas dissolvidas em água. Há evidências de que machos de Crotaphytus collaris (Crotaphytidae), uma espécie de lagarto conhecida por sua acuidade visual, é capaz de detectar e discriminar coespecíficos apenas com base em informações químicas presentes nas fezes (WILGERS & HORNE, 2009).…”
Section: Contexto Teóricounclassified